The Effectiveness Of Non-Cash Food Assistance Program (Bpnt) Management: A Case Study Of Community Perception In Wasior District, Teluk Wondama Regency, West Papua - Noak Karubuy; Farida Yuliaty; Kosasih; Vip Paramarta (LP2M IAIN Palopo, 2026)
This study aims to analyze the effectiveness of the Non-Cash Food Assistance Program (BPNT) management in Wasior District, Teluk Wondama Regency, West Papua, based on community beneficiaries' perceptions. Poverty and limited food access in this remote coastal area necessitate a rigorous evaluation of social program implementation. A qualitative case study approach was applied through in-depth interviews with five key informants beneficiary families, social facilitators, e-Warong agents, local government officials, and village heads alongside participatory observation. Thematic analysis following Miles and Huberman's model was used to process the data. The findings reveal that program effectiveness is shaped by four managerial dimensions: planning, implementation, monitoring and evaluation, and cross-stakeholder coordination. Beneficiaries acknowledged the program's contribution to food security and household budget relief; however, recurring issues such as inaccurate beneficiary data, inconsistent commodity quality, transportation constraints, and EDC machine failures hindered optimal outcomes. Coordination among Dinas Sosial, facilitators, and e-Warong agents was functional, yet village authorities remained marginalized. The study recommends periodic DTKS data updates with village-level involvement, strengthened e-Warong infrastructure, more inclusive socialization strategies, and field-based rather than merely administrative monitoring to enhance program impact in geographically challenging areas.